A Multilevel Model of Privatization in Emerging Economies - Ramamurti, Ravi (Academy of Management Review, 2000)
Why are so many emerging economies privatizing state-owned enterprises, and how does that affect their performance? The author proposes a dynamic multilevel model to answer these questions. Firm-level arguments need to be complemented by industry- and country-level arguments to explain why some enterprises are privatized but not others. Similarly, changes in firm governance resulting from privatization are only one determinant of postprivatization performance: changes in industry structure, regulation, and country-level variables are as important. Furthermore, changes introduced at all three levels in one round of reform influence the context within which subsequent privatizations occur.